The church in the modern society conformably to Gramsci - Pimenta, Eli (Universidade Estadual Paulista / UNESP, 2009)
We try to learn the thinking of Gramsci about the function of the church in the Modern Society. These functions (political, ideológica/, cultural and moral) of the church are analtzed in the perspective of the bourgeois performance and socialist movement.